Optimazion Different Feeding on Growth and Survival Rate of Tiger Grouper (Epinephelus fuscoguttatus) - Dodi Hermawan (Jurnal Perikanan dan Kelautan, 2015)
This research aim to find out about the growth and survival rate of tiger grouper (Epinephelus fuscoguttatus) that in feed with artificial feed, goldband goatfish (Upeneus moluccensis), silverbelly (Leiognathus sp.), and goldstripe sardinella (Sardinella gibbosa). Tiger grouper reared in ponds for 63 days. Tiger grouper seed used size 30 g and feed twice a day by 10% of the weight of the fish biomass. The results showed that the highest survival rate in fish feed goldband goatfish and goldstripe sardinella (100%±0.00) and the lowest in fish fed pellets and silverbelly (98.89%±1.92). The highest growth in absolute weight of fish meal which sardinella goldstripe 49.05g ± 0.20 and the lowest in fish fed pellets 42.25 g±0.20. Based on the analysis of variance showed that the meal was not significantly different (P> 0.05) on the survival rate of tiger grouper and significantly (P <0.05) on the growth of the absolute weight of absolute tiger grouper.